2003
DOI: 10.1007/bf03194268
|View full text |Cite
|
Sign up to set email alerts
|

Changes in red fox habitat preference and rest site fidelity following a disease-induced population decline

Abstract: S. 2003. Changes in red fox habitat preference and rest site fidelity following a disease-induced population decline. Acta Theriologica 48: 79-91.The habitat preferences of red foxes Vulpes vulpes (Linnaeus, 1758) in Bristol, UK, were compared during periods of high and low population density following an outbreak of sarcoptic mange (Sarcoptes scabiei). These periods are termed 'pre-epizootic' and 'post-epizootic', respectively. Habitat preferences were compared between periods during nocturnal activity and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…Specifically, the results of this study are consistent with the hypothesis that climatic variation at the onset of nutritional independence significantly affected the availability of easy-to-catch prey items, which, in turn, affected the growth and the subsequent full-grown size and mass of individual foxes. This effect was not due to habitat changes, since the key foraging habitat for foxes, back gardens (Saunders et al 1997;Newman et al 2003), has shown little pattern of change in cover or usage (Pauleit et al 2005;Smith et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the results of this study are consistent with the hypothesis that climatic variation at the onset of nutritional independence significantly affected the availability of easy-to-catch prey items, which, in turn, affected the growth and the subsequent full-grown size and mass of individual foxes. This effect was not due to habitat changes, since the key foraging habitat for foxes, back gardens (Saunders et al 1997;Newman et al 2003), has shown little pattern of change in cover or usage (Pauleit et al 2005;Smith et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Given the close relationship between home-range size and resource quality and distribution for carnivores (Gittleman and Harvey 1982), we predicted relatively smaller home ranges and no avoidance of developed areas if coyotes thrive in urban landscapes. Other species considered to be synanthropic, such as kit foxes (Vulpes macrotis), red foxes (V. vulpes), and raccoons (Procyon lotor), have smaller home ranges in urban landscapes (Cavallini 1996;Cypher, in press;Prange et al 2004), and some fox species readily use developed parts of the landscape (Cypher, in press;Newman et al 2003). Likewise, we predicted no relationship between home-range size and the proportion of the home range comprising developed land.…”
mentioning
confidence: 86%
“…For example, the spread of mange in Russia was controlled by fumigating dens with acaricides (Gerasimoff, 1958). Adults within the same social group also utilize the same den sites for resting during the day (Baker et al ., 2000), although this may change with fox density (Newman et al ., 2003). The importance of indirect transmission in the urban environment is illustrated by the concordance between levels of mange in foxes and in domestic dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Mites can persist in the environment for long periods of time, but survival off the host is dependent on ambient environmental conditions and substrate type (Arlian, Vyszenski‐Moher & Pole, 1989). Mange may also cause significant alteration of host behaviours, in some cases increasing the likelihood of transmission, but in others leading to a dramatic decline in activity (Overskaug, 1994; Skerrat, Middleton & Beveridge, 1999; Shelley & Gehring, 2002; Newman et al ., 2003; Skerrat et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%